Dietary Selenium and Whole Blood Selenium in Young Women in Iceland - Edda Ýr Guðmundsdóttir 1969- (2011)
Background: Selenium is essential for life, and in adequate amount it is required for optimal human health. Environmental conditions and agricultural practices greatly affect selenium content of foods. Nutritional bioavailability of selenium depends on the concentration and chemical forms ingested. The National Food Composition Database is an important tool in estimating intake of minerals, such as selenium, and needs regular updates with respect to selenium content of foods. Significant changes have been reported in dietary habits and food availability in Iceland that would be expected to compromise selenium intake and status, especially among young people. These include dramatic decreases in the consumption of fish and milk, as well as in selenium content of imported wheat. Aims: The aim of this present study was to assess selenium in diet and whole blood of adolescent girls in Iceland, as well as to define the most important foods contributing to selenium intake and status. Furthermore, to estimate the influence of new measurements on selenium in foods and updates on selenium data in the National Food Composition Database on the results. Methods: Subjects were 96 randomly selected healthy girls aged 16-20 years who answered a validated Food Frequency Questionnaire linked to the National Nutrition Database (ISGEM) for dietary assessment. Total selenium intake and intake from each food group was calculated as percentage contribution of each food group to selenium intake, as well as in micrograms per day. These calculations were performed twice, by older version of ISGEM and by newer one with new data from 2009 with respect to selenium content of foods. Blood samples were collected for measurement of whole blood selenium. Selenium content of major foods was analyzed during the period of blood collections and questionnaire interviews. Association between selenium status and total selenium intake and selenium intake from different food groups was assessed (Spearman´s rho), as well as the differences in median ...